A Jurnal Review KEUNTUNGAN ALGORITMA BEZIER, B-SPLINE DI DUNIA INDUSTRI - Aldi, Aldiyanra Saputra; Fauzan, Fauzan Alfarizi; Pati, Kristian Pati Wator; Zakaria, Zakaria; Ines, Ines Heidiani Ikasari (Shofanah Media Berkah, 2024)
The development of information technology has significantly influenced data management. In the past, data processing was done manually, facing several challenges such as slow processes, data input errors, difficulty in data search and analysis, and challenges in generating accurate reports. This research focuses on the utilization of Java NetBeans in various contexts, including programming training, assessment system development, administration application development in an institution, and digital school application creation. The main objective of this research is to enhance understanding in Java programming and application development. The analysis results indicate that the use of Java programming and information system approaches can provide solutions to improve efficiency, speed, and accuracy in the context of education and various other institutions. The analysis also affirms that the use of Java programming technology and a system information-based approach provides an effective solution to enhance efficiency and accuracy. The developed systems can be integrated and enhanced to meet future challenges and needs in the fields of education and military administration. Thus, the development of Java-based information systems contributes positively to improving efficiency and accuracy in data management and learning assessment processes.